1983
DOI: 10.1002/j.1460-2075.1983.tb01750.x
|View full text |Cite
|
Sign up to set email alerts
|

Quail embryo fibroblasts transformed by four v-myc-containing virus isolates show enhanced proliferation but are non tumorigenic.

Abstract: Quail embryo fibroblasts infected with any of the four natural avian myc gene‐containing virus strains (MC29, CMII, OK10 and MH2) or with the myb, ets‐containing E26 acute leukemia virus, were examined for their expression of several transformation‐associated parameters. All myc‐containing viruses, but not E26 or Rous sarcoma virus (used as a control) induced a dramatic stimulation of cell proliferation. In addition, the myc virus‐transformed cells exhibited prominent nucleoli, possibly as a consequence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(44 citation statements)
references
References 22 publications
5
39
0
Order By: Relevance
“…It has been shown that myc activation is tightly coupled to growth stimulation of quiescent cells and thus may be connected in some manner to the entry of the cells or their early passage through the Gl phase of the cell cycle (10,28). The earlier demonstrations that v-myc transformants have a significantly higher growth rate (32,38) also support the idea that myc function is related to growth control. We speculate that myc proteins may affect cell growth by their continual interaction with some form of dynamic nuclear structure which, in turn, is involved in programming the cell for proliferation.…”
Section: Downloaded Frommentioning
confidence: 88%
See 1 more Smart Citation
“…It has been shown that myc activation is tightly coupled to growth stimulation of quiescent cells and thus may be connected in some manner to the entry of the cells or their early passage through the Gl phase of the cell cycle (10,28). The earlier demonstrations that v-myc transformants have a significantly higher growth rate (32,38) also support the idea that myc function is related to growth control. We speculate that myc proteins may affect cell growth by their continual interaction with some form of dynamic nuclear structure which, in turn, is involved in programming the cell for proliferation.…”
Section: Downloaded Frommentioning
confidence: 88%
“…Recently it has been shown that the protein products of the myc, myb, and fos genes have a nuclear localization (37). Although gross subcellular location provides only a hint as to oncogene function, the nuclear localization of myc proteins (1,4,16,23) is especially intriguing in light of evidence suggesting that myc may relate to cell growth control (10,28,32,38). In addition it appears that alterations at the myc locus may be underlying events in many lymphoid and at least several nonlymphoid neoplasms in birds, rodents, and humans.…”
mentioning
confidence: 99%
“…Early studies implicated MYC in cell proliferation (Palmieri et al 1983), but it was insufficient for cellular transformation unless it cooperated with a second oncogene, RAS, to transform primary embryo fibroblasts (Land et al 1983(Land et al , 1986. In contrast, MYC alone was able to transform immortalized Rat1A fibroblasts (Eilers et al 1989).…”
Section: Transforming Activity Of Mycmentioning
confidence: 99%
“…Although the full biochemical and physiological role for phosphorylation in c-Myc remains unresolved, there are clear functional implications for phosphorylation of c-Myc. Thr-58 phosphorylation has been lost by mutation in the v-Myc proteins and in at least 60% of primary Burkitt's lymphomas (Bhatia et al, 1993), and loss of this site contributes to the enhanced transforming character of v-Myc (Frykberg et al, 1987;Palmieri et al, 1983;Filardo and Humphries, 1996;Symonds et al, 1989). Previous studies have also linked deregulated c-Myc expression with cell immortalization, and in this study we observed decreased Thr-58 phosphorylation and increased Ser-62 phosphorylation in immortalized cells relative to primary cells.…”
Section: Functional Implications For Phosphorylation Of C-mycmentioning
confidence: 99%
“…The loss of Thr-58 is found in the majority of v-Myc proteins (Papas and Lautenberger, 1985) and in c-Myc proteins from Burkitt's lymphomas (Bhatia et al, 1993). v-Myc proteins that have not lost Thr-58 are weakly transforming relative to v-Myc proteins that have lost Thr-58 (Palmieri et al, 1983;Chen et al, 1989). Restoring Thr-58 to the MC29 v-Myc protein restrains its ability to transform ®broblasts and myelomonocytic cells (Symonds et al, 1989), while mutating Thr-58 in c-Myc to an alanine increases its ability to induce foci in embryo ®broblasts (Frykberg et al, 1987).…”
Section: Introductionmentioning
confidence: 99%